Synthesis of 3-Substituted Phenacyl-5-[2-phenyl-4H-4-oxo-1-benzopyran-6-yl)methylenyl]-thiazolidine-2,4-diones and Evaluation of Their Antimicrobial Activity - Ayhan-Kilcigil, Gülgün; Altanlar, Nurten (Arzneimittelforschung, 2000)
Synthesis and physico-chemical properties of two 3-substituted phenacyl-thiazolidine-2,4-di-ones (2c-d) and four 3-substituted phenacyl-5-[2-phenyl-4H-4-oxo-1-benzopyran-6-yl)methyl-enyl]-thiazolidine-2,4-diones (4a-d) are described. These products were synthesized by Knoe-venagel reaction from flavone-6-carboxaldehyde (3) and 3-(substituted phenacyl)-thiazolidine-2,4-diones (2a-d). Antibacterial and antifungal activities were investigated for these compounds.
Keywords: Flavonyl-thiazolidinediones; Phenacyl-thiazolidine-2,4-diones; antifungal and antimicrobial activity, 3-substituted, synthesis